COVID-19 associated rhino-orbital-cerebral mucormycosis with underlying diabetes mellitus - Saparbek Satmurzayev; Natalia Selivokhina; Malika Khaiitova; Aida Seitaliyeva; Murat Nurlybaev (National Scientific Medical Center, 2022)
Introduction: Since the beginning of the COVID-19 pandemic, there has been an increase in opportunistic infections such as mucormycosis, which is of some concern given the fairly rapid spread. The development of immunosuppression associated with COVID-19, coupled with the presence of comorbidities that exacerbate the progression of the disease and in some cases lead to a fatal outcome, plays an important role in this. Case presentation: We have examined a real case of rhino-orbital-cerebral mucormycosis in comparison with earlier published contemporary studies on epidemiology, clinical manifestations, and risk factors. Autopsy materials of nasal mucosa, eye socket, brain of a patient with COVID-19 associated with diabetes mellitus have been subjected to a histological study. Conclusion: The presented case demonstrates a unique pathomorphological pattern of rhino-orbital-cerebral mucormycosis, first registered in Kazakhstan and of great interest in the world practice.